An effective capacity for generation reliability evaluation of renewable power plant - Kunjana Chaiamarit (2018)
The equivalency between renewable and conventional capacities and their contribution on generation reliability are investigated by using the concept of effective capacity, which has two definitions. The effective capacity can be computed from generation capacities of renewable and conventional power plants as well as effective load carrying capability. Forced outage rate, generation capacity, and number of renewable units are varied to reflect operation behavior of renewable power plant. Loss of load probability is considered as generation reliability index. A small test model consists of three conventional units with an addition of a unit of interest. © 2014 IEEE.